2020
DOI: 10.1259/bjr.20200870
|View full text |Cite
|
Sign up to set email alerts
|

Improving rib fracture detection accuracy and reading efficiency with deep learning-based detection software: a clinical evaluation

Abstract: Objectives: To investigate the impact of deep learning (DL) on radiologists’ detection accuracy and reading efficiency of rib fractures on CT. Methods: Blunt chest trauma patients (n = 198) undergoing thin-slice CT were enrolled. Images were read by two radiologists (R1, R2) in three sessions: S1, unassisted reading; S2, assisted by DL as the concurrent reader; S3, DL as the second reader. The fractures detected by the readers and total reading time were documented. The reference standard for rib fractures was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 28 publications
2
26
1
Order By: Relevance
“…A CNN for the automatic detection of acute rib fractures is expected to detect all types of acute fractures. The diagnostic performance of radiologists in our study was lower for non-displaced fractures than displaced fractures, and this was in line with previous studies [21,22,25]. However, the assistance of CNN significantly improved the performance of radiologists for the detection of non-displaced fractures.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…A CNN for the automatic detection of acute rib fractures is expected to detect all types of acute fractures. The diagnostic performance of radiologists in our study was lower for non-displaced fractures than displaced fractures, and this was in line with previous studies [21,22,25]. However, the assistance of CNN significantly improved the performance of radiologists for the detection of non-displaced fractures.…”
Section: Discussionsupporting
confidence: 91%
“…Based on our study, the adoption of CNNs for the detection of acute rib fractures on CT images may not only improve the radiologists' detection accuracy of fractures by using as a second opinion but also reduce the time required for reading CT images. However, in our study, the sequential test method [25] was used in the observer performance study. Therefore, we could not independently compare the reading time with images alone and the reading time with images using the CNN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To avoid serious consequences, accurate detection of rib fractures is important. Low-dose thoracic computed tomography (CT) scans are commonly used in the assessment and auxiliary diagnosis of rib fractures [ 3 , 4 ], but missed diagnoses are common. Studies have shown that the sensitivity of diagnosis of rib fractures is only about 60% on initial chest CT evaluations [ 5 ], and missed diagnosis may cause severe medical accidents.…”
Section: Introductionmentioning
confidence: 99%